Bibliometric Research Trends of Local Wisdom in Science Education: Mapping Publications, Collaborations, and Implications - Sutrimo, Moh Slamet; Retnawati, Heri; Ulwiyah, Sa’adatul; Fauzan, Muh Ikhwan; Salsabila, Azkiya; Iqbal, Muhammad (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This study aims to map research trends related to local wisdom in educational science through a bibliometric approach. By analyzing 64 articles obtained from the Scopus database from 2009 to 2024, this study explores publication patterns, cross-country collaborations, dominant keywords, relevant topics, and their implications. The analysis was carried out with the help of the R program application. The results show that publications related to local wisdom have experienced a significant increasing trend from previous years. Indonesia is the main contributor with institutional affiliations such as Padang State University and Surabaya State University. Local wisdom keywords dominate with a strong relationship to science learning and character education. This study is able to provide an overview of the importance of research related to local wisdom related to educational science and provide important insights regarding the integration of local wisdom in science to support the sustainability of local culture while meeting the challenges of global education. Keyword co-analysis reveals that â€œlocal wisdomâ€ frequently co-occurs with themes such as science education, character education, and ethnoscience, reflecting efforts to contextualize science learning within cultural frameworks. While the integration of local wisdom presents potential for curriculum development and culturally responsive pedagogy, these implications should be interpreted within the scope of the descriptive bibliometric findings. Further research is recommended to explore practical models and cross-national collaboration strategies. Futre recommendation is for developing a model for integrating local wisdom into STEM and character-based education.